Emigration Policy and State Governments in Mexico - Guillermo Yrizar Barbosa; Rafael Alarcón (El Colegio de la Frontera Norte, A.C., 2010)
Several Mexican state governments have created institutions and developed public policies to benefit their emigrants abroad following the federal government's lead. The main objective of this article is two-fold: first, to analyze the three sociopolitical factors that influenced the emergence of emigration policy at the state level, and second, to examine two strategic activities undertaken by state governments in the Central Western region. Public agencies for international migrants carry out various actions such as administering federal government programs, preserving regional identities, promoting human and civil rights for migrants, locating missing persons, and processing official documents. Many of these activities are complementary to those undertaken by federal government. However, some of these agencies play a strategic role in the repatriation of the bodies of Mexican migrants that die in the United States and the management of temporary employment abroad for their citizens.